Towards Understanding the Effects of Web 2.0 at the Project Level Knowledge Management on Projects’ Success - Nath, Anupam Kumar (Journal of Accounting, Business and Management (JABM), 2021)
Web 2.0 is in use for knowledge management (KM) in organizations at different levels. In this research, we study the relationship between the use of Web 2.0 in knowledge management (KM) and its effect on the Project's success when Web 2.0 is in use for the project's KM. We also study the impact of project-level KM context variables on this relationship. Findings show that the uses do not have a decisively positive effect